2014
DOI: 10.1002/jez.b.22604
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a retinoic acid receptor (RAR)-like protein in the embryonic and adult nervous system of a protostome species

Abstract: The vitamin A metabolite, retinoic acid, is an important molecule in nervous system development and regeneration in vertebrates. Retinoic acid signaling in vertebrates is mediated by two classes of nuclear receptors, the retinoid X receptors (RXRs) and the retinoic acid receptors (RARs). Recently, evidence has emerged to suggest that many effects of retinoic acid are conserved between vertebrate and invertebrate nervous systems, even though the RARs were previously thought to be a vertebrate innovation and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 52 publications
7
45
0
Order By: Relevance
“…We have also shown that immunoreactivity for LymRAR is present in developing neurons in the CNS and associated with the developing shell (Carter et al, 2015). We have also shown that immunoreactivity for LymRAR is present in developing neurons in the CNS and associated with the developing shell (Carter et al, 2015).…”
Section: Do Rar Agonists Mimic the Effects Of Endogenous Retinoids supporting
confidence: 53%
See 3 more Smart Citations
“…We have also shown that immunoreactivity for LymRAR is present in developing neurons in the CNS and associated with the developing shell (Carter et al, 2015). We have also shown that immunoreactivity for LymRAR is present in developing neurons in the CNS and associated with the developing shell (Carter et al, 2015).…”
Section: Do Rar Agonists Mimic the Effects Of Endogenous Retinoids supporting
confidence: 53%
“…Antigen preadsorbed controls for this antibody were previously performed on Lymnaea neurons (Carter et al, 2015), so here, control experiments only omitted the primary antibody, and the regenerating PeA cells did not demonstrate any RAR immunoreactivity (0/27 cell bodies and 0/23 growth cones; data not shown). These data support our previous findings (Carter et al, 2015) that LymRAR can be found in nonsomatic compartments such as neurites and growth cones. Representative example of a PeA growth cone before (i; t = 0 min) and after responding to a gradient of atRA (ii; t = 16 min).…”
Section: Lymrar Plays a Role In Axon Guidancementioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, a specific RAR subtype, RARÎČ, has been shown to increase in a stage-specific manner during CNS regeneration in the adult newt [13]. As both RXR and RAR are likely critical during RA-induced regeneration [13,77], and expressed in Lymnaea PeA growth cones [19,20], it is possible that miR-124 could be targeting either mRNA sequence during specific stages of regeneration. Indeed, the 3 UTR of the Lymnaea RAR and RXR mRNAs contain potential binding sites for miR-124, though we have not yet explored whether these mRNAs are found locally in the neurites and/or growth cones.…”
Section: Role Of Mir-124 During Ra-induced Cns Regenerationmentioning
confidence: 99%